CD44 and CD24 Expression and Prognostic Significance in Canine Mammary Tumors. Issue 3 (May 2019) - Rogez, Bernadette; Pascal, Quentin; Bobillier, Audrey; Machuron, François; Lagadec, Chann; Tierny, Dominique; Le Bourhis, Xuefen; Chopin, Valérie
CD44 + /CD24 – phenotype has been used to identify human and canine mammary cancer stem-like cells. In canine mammary tumors, CD44 + /CD24 – phenotype has been associated with high grade and lymph node infiltration. However, several studies have reported opposing results regarding the clinical significance of phenotypic groups formed by the combination of CD44 and CD24 in both human and canine mammary tumors. So far, no study has investigated the correlation between these phenotypes and survival in dogs. The aim of this study was to investigate the expression and distribution of CD44 and CD24 in canine mammary carcinomas and to correlate them with histological diagnosis and survival in a well-characterized cohort. Immunohistochemistry was performed in 96 mammary carcinomas with antibodies against CD44 and CD24. Expression of CD44 + and CD44 + /CD24 – phenotype was detected in 75 of 96 (78%) and 63 of 96 (65.6%) carcinomas, respectively. Their expression was associated with tumor type, occurring more often in tubular complex carcinomas than in solid carcinomas. CD44 + /CD24 – phenotype was associated with a better overall survival ( P = .001). CD24 + expression was detected in 52 of 96 tumors (54%) and CD44 – /CD24 + phenotype in 39 of 96 tumors (40.6%). Both were associated with poor clinicopathological parameters (high grade, and emboli). No correlation with overall survival was observed. CD44 + /CD24 – expression was associated with a better prognosis and occurred at high frequency and high level, indicating that this phenotype is not suitable to detect cancer stem cells in canine mammary carcinomas. Although further studies are needed, our results suggest that CD24 may constitute a valuable marker of poor prognosis for canine mammary carcinomas.